2020
DOI: 10.1021/acs.jchemed.0c00745
|View full text |Cite
|
Sign up to set email alerts
|

When the Kitchen Turns into a Physical Chemistry Lab

Abstract: We present our experience with transferring a four-day photometry and dye-adsorption laboratory experiment to the kitchens of students of Applied Thermodynamics from our degree in “Industrial Chemical Process Engineering”. The students designed and built a double-beam photometer using their smartphones and household materials, then prepared a series of dye-solutions with well-known relative concentrations and measured the absorbance–concentration calibration curve. After 24 h of adsorption to kitchen absorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 12 publications
0
51
0
Order By: Relevance
“…In 2020–2021, some laboratory experiments were carried out using digital images. We could cite polymer degradation, determination of iron­(III) in water, calculation of food dye adsorption isotherms, quantitative analysis of food dyes, determination of biodiesel content in diesel oil, the analysis of salivary amylase using starch from food as a substrate, and determination of starch in banana …”
Section: Introductionmentioning
confidence: 99%
“…In 2020–2021, some laboratory experiments were carried out using digital images. We could cite polymer degradation, determination of iron­(III) in water, calculation of food dye adsorption isotherms, quantitative analysis of food dyes, determination of biodiesel content in diesel oil, the analysis of salivary amylase using starch from food as a substrate, and determination of starch in banana …”
Section: Introductionmentioning
confidence: 99%
“…Recent research in chemical education has shown that an overwhelming majority of students who participate in kitchen chemistry voice satisfaction with it, even in distance courses that were rapidly forced into it from a traditional setting . In order to keep students on track with the assignments, the experiments can be accompanied by a synchronous instruction session before each experiment, where the professor may review relevant concepts . Of course, the TA and professor may be available for video conferencing during experimentation, but only if synchronous experimentation is selected for the course.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many papers appeared on various aspects of applying these principles. The recent COVID 19 pandemic-stricken era with extensive campus lockdowns resulted in canceled scheduled practical activities for chemistry students, just to witness a further impetus to this approach. The sudden constraint of switching to online education is well exemplified by a 1000+ pages long special issue of Journal of Chemical Education on “Insights gained while teaching chemistry in the time of COVID 19” with over 180 articles enlisting dozens of papers devoted to exploitation of experiments based on household items, consumer products, kitchen settings, and in general, experiments carried out at home . This fact motivates the urgent reconsideration of the role of classical laboratory experiments in chemistry education. , …”
Section: Methodsmentioning
confidence: 99%